Progress in Triboelectric Materials: Toward High Performance and Widespread Applications. (17th April 2019) - Yu, Aifang; Zhu, Yaxing; Wang, Wei; Zhai, Junyi
Abstract: Triboelectric phenomena can be observed everywhere; however, they are consistently omitted from applications. Although almost all substances exhibit a triboelectrification effect in daily life, chemists as well as materials scientists have performed extensive investigations in both the aspects of basic science and practical applications to promote the development of triboelectric nanogenerators (TENGs). Here, a detailed survey of materials engineering for high triboelectric performance and multifunctional materials toward specific applications is summarized, including constructing micro/nanostructures, chemically modifying the frication surface, modulating bulk friction materials, the mechanism for improved performance, and preparing materials for implantable medical devices, bionic skin, and wearable electronic devices. Moreover, an in depth discussion of the current challenges and future efforts for strengthening the performance of TENGs is elaborated in detail, which will better guide new researchers toward a deeper understanding of and explorations about TENGs. Abstract : A detailed survey of materials engineering for high triboelectric performance and multifunctional materials toward specific applications is summarized. Moreover, an in‐depth discussion of the current challenges and future efforts for strengthening the performance of triboelectric nanogenerators is provided.